Tinjauan Rehabilitasi Pekerjaan Jalan Pada Jalan Cempa II Desa Mattunru Tunrue Kecamatan Cempa Kabupaten Pinrang - Novianti, Novianti; Rahmawati, Rahmawati; Hamka, Hamka (Institut Teknologi Garut, 2024)
This research is motivated by the fact that Mattunru Tunrue Village is one of the villages in Cempa District, Pinrang Regency, South Sulawesi Province, Indonesia. In this village there are marine tourism attractions, namely Harapan Ammani Beach and Dewata Wakka Beach and the Karasa industrial center with sufficient accessibility. both via the Cempa II road, which is currently experiencing damage, which is a concern for the people of Mattunru Tunrue Village and of course road users. The aim of the research is to determine the type of road damage found on Cempa Road, Mattunru Tunrue Village, Pinrang Regency, as well as the level of damage that occurs and determine the appropriate type of road maintenance. Knowing the methods used in concrete road rehabilitation work on Jalan Cempa, Mattunru Tunrue Village, Pinrang Regency. The research method for data analysis uses the Bina Marga Method. To achieve this goal, primary data is needed that can be surveyed in the field regarding the type of road damage, level of road damage and traffic volume surveys. The results of this research show that the road conditions experienced damage such as holes, raveling, delamination and wear. The LHR value of the Cempa road section, Mattunru Tunrue Village, Pinrang Regency on weekdays is 3635 pcu/day and on holidays it is 3336 pcu/day so the road class value on Cempa road is class 5. The rehabilitation method used on Cempa II road namely using a type of continuous cement concrete pavement with reinforcement. The width of the road being made is wider than the previous construction, namely according to the work drawings, namely 5 meters using concrete construction with a road height of 20cm.